Sucessão em empreendimentos sociais : uma análise de múltiplos casos em Uberlândia-MG - Arruda, Daniela Vasconcelos (2014)
The social entrepreneurship has your origin in various initiatives: non-profit organizations, mature social projects, and can still be found in strategic alliances between organizations from different sectors. Many are the objectives that this movement seeks to reach, such as the increasing income of the poorest segments of the population, solidarity cooperation for mutual credit, microcredit for small businesses, health, education and assistance where these public services are scarce. Such actions institute changes, even small and subtle, in social and economic relations of capitalist structure (GODÓI-DE-SOUSA; FISCHER, 2012). Although plenty have been studied and researched about the subject, still remain gaps to be filled in the theory, one refers to the succession process in these organizations, which plays an important role in its continuity. Thus, the objective of this research was to investigate how the succession process occurs in Uberlândia-MG social entrepreneurship in light of Godói-de-Sousa three-dimensional model, aiming to identify specific features. The model mentioned is one of the first which are known in the literature and was built specifically for the analysis of the succession process in social entrepreneurship. The research, of an applied nature, intended to generate knowledge for practical application in the studied organizations. With descriptive character and an approach of qualitative nature, then was tried to, at a first moment, execute a survey of the social entrepreneurship located in Uberlândia-MG, cataloging the number of 210. Then, a questionnaire was applied via telephone and was obtained a result of 78 answered. Among these, another questionnaire was applied in order to understand its performance and identify what had passed or were passing through a succession process. After, approximately, two months, 21 organizations returned and, from these, were selected four that composed the multiple case studies. The data collection of this research consisted of interviews with various stakeholders, field observations and analysis of organizations documents. Through the analysis of results it was found that leaders of social entrepreneurship do not prepare their successors previously and, mostly, members are not interested in taking responsibility in the Board; such organizations do not plan the succession process and, still, there is no involvement of the external context in this process and, neither, stakeholders are interested in participating.